ARTIFICIAL INTELEGENCE (AI) DAN POLITIK: ANALISIS TERHADAP PERAN DAN SIGNIFIKANSI AI DALAM KOMUNIKASI POLITIK 2024 DI INDONESIA - Arifin, Moh. Samsul (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
In this digital era, Artificial Intelligence (AI) has emerged as a profound and innovative tool across various aspects of human life—including entertainment, economy, education, and increasingly, the political sphere. The rapid development of AI in recent years has shown significant impact, including its involvement in political party decision-making processes. This study explores the political relevance of AI utilization within the realm of political communication, focusing on the analysis of its role and significance in the dynamics of Indonesia’s 2024 general election campaign. The aim is to examine AI’s potential in the political landscape by identifying the types of AI employed, both as supporting tools and in other assistive capacities. Through a qualitative approach, this research investigates the impact of AI on modernizing political campaign strategies, enhancing the efficiency of political communication, and influencing decision-making processes within political contexts. The methodology includes content analysis of campaign materials involving AI technologies and observation of political interactions mediated by artificial intelligence. Accordingly, this study seeks to provide an in-depth understanding of how the utilization of AI in political campaigns can shape political dynamics, public opinion, and democratic processes in Indonesia. The findings reveal that AI has been employed not only as a tool for generating visual content and political narratives but also as a strategic communication medium to shape voter perception and increase public engagement. Generative AI technologies, such as image generators, have demonstrated emotional appeal in political campaigns, as evidenced in the campaigns of Prabowo-Gibran and Andra-Dimyati. These findings indicate that AI contributes significantly to the transformation of modern political communication, influencing both public opinion and the democratic process in Indonesia.